2019
DOI: 10.1016/j.phro.2019.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Development of a multicentre automated model to reduce planning variability in radiotherapy of prostate cancer

Abstract: A B S T R A C TBackground and purpose: Inter-institutional studies highlighted correlation between consistent radiotherapy quality and improved overall patient survival. In treatment planning automation has the potential to address differences due to user-experience and training, promoting standardisation. The aim of this study was to evaluate implementation and clinical effect of a multicentre collaboratively-developed automated planning model for Intensity-Modulated Radiation Therapy/ Volumetric-Modulated Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…The model has learned achievable dose volume histograms from a library of plans, in which OAR dose depends on the geometric relationship between a target and OAR, beam geometry and prescription dose. KBP has been used to improve the consistency and efficiency of treatment planning in routine practice, to audit treatment plan quality within and external to an institution, and to retrospectively review treatment plan quality in clinical trials [10,[13][14][15][16][17][18][19][20][21]. In retrospective review of clinical trial data, the potential of KBP to improve individual patient OAR dosimetry has been demonstrated [13,16,17,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The model has learned achievable dose volume histograms from a library of plans, in which OAR dose depends on the geometric relationship between a target and OAR, beam geometry and prescription dose. KBP has been used to improve the consistency and efficiency of treatment planning in routine practice, to audit treatment plan quality within and external to an institution, and to retrospectively review treatment plan quality in clinical trials [10,[13][14][15][16][17][18][19][20][21]. In retrospective review of clinical trial data, the potential of KBP to improve individual patient OAR dosimetry has been demonstrated [13,16,17,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] RapidPlan (RP) which is integrated in the Eclipse treatment planning system (TPS) (Varian Medical Systems, Palo Alto, CA, USA) is a specific knowledge-based planning (KBP) solution that can reduce the variation of dose-volume parameters and ensure planning consistency between planners and institutions. [6][7][8][9][10][11] Many studies reported that RP using a single optimization of dose-volume parameters and dose distributions can produce IMRT/VMAT plans superior or comparable to clinically accepted plans for various treatment sites. [12][13][14][15][16][17][18][19][20][21][22][23][24][25] The RP model performance, such as sparing of OARs, depends on the training plans included in the model library; therefore, the registration of better plans is useful to update the model and enhance its performance.…”
Section: Introductionmentioning
confidence: 99%
“…However, coverage of the target and sparing of the organs at risks (OARs) with inverse planning depends on the planner's or institution's experience and protocol compliance, and can therefore compromise the gains of high‐precision radiotherapy 2–5 . RapidPlan (RP) which is integrated in the Eclipse treatment planning system (TPS) (Varian Medical Systems, Palo Alto, CA, USA) is a specific knowledge‐based planning (KBP) solution that can reduce the variation of dose–volume parameters and ensure planning consistency between planners and institutions 6‐11 12‐25 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…a contoured planning CT-scan. Panettieri et al [20] presented in this journal their results on a multi-centric investigation where a KBP model for prostate (based on commercial planning system) was developed, trained and validated by two centers and then distributed, re-validated according to local practice guidelines and then utilized clinically by six other institutions. The authors suggested the feasibility of developing and implementing at a multi-centric level an automated planning workflow.…”
mentioning
confidence: 99%